Attempted suicide leading to acquired brain injury: a scoping review. (28th January 2020) - Higgins, Ciara; Rooney, Katy; O'Connell, Barbara; Waldron, Brian; Linehan, Christine
ABSTRACT: Objective : Conduct a scoping review of literature surrounding acquired brain injury (ABI) sustained secondary to a suicide attempt to establish the current body of research on injury outcomes and rehabilitative needs for this population. Methods : A systematic search of the literature was conducted. Searches were conducted using terms relating to this injury etiology and search results with original or secondary data on individuals with an ABI were included for review. Results : Thirty-two articles were reviewed. Limited data characterizing this population exists in the literature. Findings indicate that this population have generally poorer injury outcomes compared with ABI sustained through other means. Rehabilitative needs are rarely addressed, but limited commentary suggests that extensive pre-morbid conditions, severity of injuries and psychosocial support needs of this population present implications for rehabilitative supports. Conclusion : There is a relative dearth of research examining ABI sustained secondary to a suicide attempt. Collated findings suggest these individuals are rarely recognized in the literature as a distinct ABI population with rehabilitative needs specific to this etiology. Future research should aim to address the gaps identified in the literature, including characterizing the population, establishing pre-morbid conditions and developing tailored rehabilitative support to address complex needs.